Kuwait : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes budget financing options and their potential macro-financial implications for Kuwait. With large financial buffers and low debt, Kuwait has substantial room to finance the emerging fiscal deficits. The financing strategy should be underpinned by sound institutional and legal reforms and geared toward the development of the domestic debt markets. A balanced mix of asset drawdown and borrowing from a diversified investor base (nonresidents, domestic banks and nonbank financial institutions) would help mitigate negative implications for the economy and develop the corporate debt market.